Of linguicide and resistance: children and English instruction in nineteenth-century Indian boarding schools in Canada. (2nd November 2017) - Griffith, Jane
Abstract: Indian residential schools lasted in Canada for nearly 150 years, with the last one closing in 1996. Canada's recently concluded Truth and Reconciliation Commission has confirmed what Indigenous families have said all along: many Indigenous children endured abuse, prolonged separation between parent and child, and intergenerational legacies. Thousands of children died while attending school. Indian residential schools were one of Canada's many colonial strategies, which aimed to inculcate students in a British world view and assimilate them by denigrating their spiritualities, epistemologies, and relationships to land. Indian residential schools also attacked Indigenous languages and insisted on English only. While historical studies of teaching English often elide a broader history of colonialism, this paper uses a settler colonial studies analysis to read nineteenth-century government reports as well as school newspapers to uncover how nineteenth-century Indian boarding schools publicly conceived of the teaching of English; my reading of nineteenth-century archival documents is informed by survivor testimony and memoir that help to puncture the propaganda of government and school documentation. Informed by the work of Wallace Lambert and Ruth Spack, I argue that school documentation represented English only rather than the more complicated understanding of English and – English in addition to Indigenous languages. This distinction critically separates the policies of government and school from the beliefs of many parents and children, who learned English for their own reasons but not at the expense of another language.